THE IMPACT OF EMPLOYEE ENGAGEMENT ON TALENT MANAGEMENT AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE IN THE SOCIAL SECURITY ADMINISTRATION FOR EMPLOYMENT AT THE MAIN BRANCH OFFICE SURAKARTA - Laksono Sumarto; Mrihrahayu Rumaningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The objectives of this study are (1) To examine and analyze the partial impact of talent management and knowledge management on employee performance at the Main Branch Office of Social Security ( BPJS) Surakarta. (2) To examine and analyze the impact of employee engagement mediation on the impact of talent management and knowledge management on employee performance at the main branch office of Social Security (BPJS)Surakarta. This research was conducted in Surakarta, by taking the subject of employees at the Social Security (BPJS) Surakarta Main Branch which consists of several District Operational Service Offices (KLOK Kantor PelayananOperasionalKabupaten), namely KLOK Karanganyar, KLOK Sragen, KLOK Wonogiri and KLOK Sukoharjo. The results of the study found that the direct impact and indirect impact indicate that both pathways are effective, so that the Talent Management and Knowledge Management variables need to be maintained. The direct impact of Talent Management is greater than the indirect impact, while the direct impact of Knowledge Management is smaller than the indirect impact. There are positive and significant direct and indirect impacts between Talent Management and Knowledge Management on employee performance, so that employee attachment mediation as a mediating variable is partial mediation. Keywords: Talent Management, Knowledge Management, Employee Engagement, Employee Performance, Path Analysis.